2017
DOI: 10.1016/j.nicl.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in microstructural white matter metrics in Alzheimer's disease

Abstract: BackgroundAlzheimer's disease (AD) is a progressive neurodegenerative disorder. Current avenues of AD research focus on pre-symptomatic biomarkers that will assist with early diagnosis of AD. The majority of magnetic resonance imaging (MRI) based biomarker research to date has focused on neuronal loss in grey matter and there is a paucity of research on white matter.MethodsLongitudinal DTI data from the Alzheimer's Disease Neuroimaging Initiative 2 database were used to examine 1) the within-group microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
86
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 55 publications
19
86
0
10
Order By: Relevance
“…Using FA, MD, AxD and RD to analyze the integrity of anatomical white matter tracks, we showed for each DTI scalar that MCI A+N+ displayed an early alteration of the white matter in the fornix (columns and body and right crus of the fornix; these structures are shown in the supplementary Figure S7). The fornix belongs to the Papez circuit, is known to play an important role in memory and has been shown to be impaired in AD (Caso et al, 2015;Delano-Wood et al, 2012;Laxton et al, 2010;Mayo et al, 2017;Molinuevo et al, 2014;Nowrangi and Rosenberg, 2015;Wisse et al, 2015). Thus, in agreement with previous studies, we showed that the breakdown of the biomarker positive groups display specific connectome changes as compared to MCI subjects with normal biomarkers.…”
Section: Patients Positive For Both Biomarkers Of Amyloid and Neusupporting
confidence: 91%
See 1 more Smart Citation
“…Using FA, MD, AxD and RD to analyze the integrity of anatomical white matter tracks, we showed for each DTI scalar that MCI A+N+ displayed an early alteration of the white matter in the fornix (columns and body and right crus of the fornix; these structures are shown in the supplementary Figure S7). The fornix belongs to the Papez circuit, is known to play an important role in memory and has been shown to be impaired in AD (Caso et al, 2015;Delano-Wood et al, 2012;Laxton et al, 2010;Mayo et al, 2017;Molinuevo et al, 2014;Nowrangi and Rosenberg, 2015;Wisse et al, 2015). Thus, in agreement with previous studies, we showed that the breakdown of the biomarker positive groups display specific connectome changes as compared to MCI subjects with normal biomarkers.…”
Section: Patients Positive For Both Biomarkers Of Amyloid and Neusupporting
confidence: 91%
“…Moreover, looking at MD, AxD and RD, we also highlighted an alteration of the superior fronto-occipital fasciculus bilaterally. While they are not well explained by the specific neurodegeneration process, these alterations of corona radiata and superior-occipital fasciculus have already been reported in previous studies (Gold et al, 2014;Mayo et al, 2017;Meng et al, 2012;Molinuevo et al, 2014). Because these alterations were also displayed by MCI A-N+ and MCI A+N-subgroups (but not by MCI A-N-), we hypothesized that these mild white matter alterations without associated FA decrease were more linked to a small non-specific neurodegeneration process, rather than a specific AD-linked neurodegeneration process.…”
Section: Patients Positive For Both Biomarkers Of Amyloid and Neumentioning
confidence: 55%
“…This is consistent with previous reports, where microstructural changes were studied in the context of brain regional hypometabolism by FDG-PET, and in which metabolic and WM tract changes were shown to expand to the temporal lobe and posteriorly in an AD pattern (Cross et al, 2013) A longitudinal study using the ADNI data reported change over time in the hippocampal cingulum in patient with AD (Mayo et al, 2017) Early OT involvement was reported in Parkinson disease associated OID as well. (Rolheiser et al, 2011) Rolheiser, et al report decreased FA within an olfactory ROI similar to the region studied in our analysis.…”
Section: Discussionsupporting
confidence: 91%
“…(Cross et al, 2013) Interestingly, longitudinal observation of regional white matter ultrastructure demonstrated exclusive changes in the hippocampal cingulum in AD as compared to normal aging. (Mayo et al, 2017) These data suggest that the mechanism of OID in aging and in AD and AD-associated aMCI may be different. This cross-sectional study was designed to assess microstructural changes using DTI in subjects with aMCI, AD and NCs and to compare and contrast them in the context of the olfactory phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…Both cross-sectional and longitudinal studies of neurodegenerative disorders have reported encouraging results regarding the use of DWI as a biomarker for disease progression (Bozzali et al, 2002; Canu et al, 2010; Goveas et al, 2015; Gregory et al, 2015; Harrington et al, 2016; Mayo et al, 2017; Phillips et al, 2014; Phillips et al, 2016; Poudel et al, 2015; Stricker et al, 2009; Weaver et al, 2009; Weiler et al, 2015; Yu et al, 2009). While studies in PD have reported cross-sectional differences in DWI measures between PD and control subjects (Agosta et al, 2014; Bertrand et al, 2012; Duncan et al, 2016; Goveas et al, 2015; Hattori et al, 2012; Melzer et al, 2013; Rae et al, 2012; Zhang et al, 2011), information regarding differential progression of WM change between PD patients and normal aging adults is relatively limited (Melzer et al, 2015; Rossi et al, 2014; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%